One-pot synthesis of C-2-symmetric N,N '-diaryl bis(oxazolidin-2-ones) as precursors for N,N '-diaryl 2,3-diamino-1,4-butanediols - Lee, S; Lim, CW; Lee, JK; Jung, OS; Lee, YA (PERGAMON-ELSEVIER SCIENCE LTD, 2000)
A new and general one-pot synthetic method for C-2-symmetric N,N'-aryl-disubstituted bis(oxazolidin-2-ones) has been developed. Highly regioselective intramolecular cyclization reactions of 2,3-di(methanesulfonyloxy)-1,4-dihydroxybutane with arylisocyanates in the presence of sodium hydride afforded the corresponding C-2-symmetric N,N'-aryl-disubstituted bis(oxazolidin-2-ones) in 82-92% yields. Hydrolytic ring opening of the bis(oxazolidin-2-ones) provided a convenient synthetic route for optically pure C-2-symmetric N,N'-aryl-disubstituted 2,3-diamino-1,4-butanediols (58-86% yields). (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: BIFUNCTIONAL CHIRAL AUXILIARIES; OXAZOLIDINONE ANTIBACTERIAL AGENTS; ASYMMETRIC-SYNTHESIS; VICINAL DIAMINES; STEREOSELECTIVE SYNTHESIS; AMINO-ACIDS; EFFICIENT SYNTHESIS; 2,3-EPOXY ALCOHOLS; ALDOL REACTIONS; TARTARIC ACID